Development of Tabletop Game Based on Problem-Based Learning to Enhance Fifth-Grade Students’ Critical Thinking Skills on Flora and Fauna Distribution - Ulandari, Elsa Nadya; Fatih, Mohamad; Amalia, Shofi Nur (Jurnal Gentala Pendidikan Dasar, 2026)
This study was motivated by the low critical thinking skills of fifth-grade students at SDN Ngaringan 03, Blitar Regency, in learning the topic of flora and fauna distribution. Teacher-centered instruction and the limited use of learning media have resulted in students being less active in analyzing and solving problems. This study aimed to develop a Problem-Based Learning (PBL)-based tabletop game, determine its feasibility, and improve students' critical thinking skills. The research employed the Research and Development (R&D) method using a modified Borg and Gall model consisting of seven stages: research and information gathering, planning, product development, expert validation, limited field testing, product revision, and field testing. Data were collected through observations, interviews, questionnaires, and critical thinking tests. The results indicated that the PBL-based tabletop game was feasible for classroom use, engaging for students, and effective in enhancing students’ participation and critical thinking skills in learning flora and fauna distribution